2018
DOI: 10.4103/0973-1482.171369
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum survivin level in early diagnosis of cancer

Abstract: Our study results may suggest that high serum survivin levels can show 4 times increased risk of cancer in a subject with a high suspicion of cancer. Furthermore, survivin level was not influenced with demographic characteristics of breast, gastric, colorectal, prostate, ovarian cancer, and glioblastome multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…There has been also many studies showing that urine BIRC5 level can be used as a diagnostic indicator of bladder cancer ( Weikert et al, 2010 ) and lung cancer ( Wu et al, 2009 ). Recently, serum BIRC5 levels has been found to be positively linked to early diagnosis in majority of human cancers ( Gunaldi et al, 2018 ). Here, we proposed how BIRC5 is involved in RFWD3-mediated CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…There has been also many studies showing that urine BIRC5 level can be used as a diagnostic indicator of bladder cancer ( Weikert et al, 2010 ) and lung cancer ( Wu et al, 2009 ). Recently, serum BIRC5 levels has been found to be positively linked to early diagnosis in majority of human cancers ( Gunaldi et al, 2018 ). Here, we proposed how BIRC5 is involved in RFWD3-mediated CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…In the human genome, the gene encoding BIRC5 is among one of the highly specific tumor genes (79) that prevent apoptosis by inhibiting the activity of different caspases (80), leading to aggressive tumor behavior and poor clinical outcomes (81). Compared to normal tissues, an increase in BIRC5 expression has been demonstrated in different types of cancers, including pancreatic (82), lung (83), colon and ovarian (84), esophageal and skin (85), colorectal and lymphoma (86) and prostate (87). In particular, in TNBC cells, the highly expressed BIRC5 is considered a marker in the early diagnosis of BC and was found to correlate with the resistance to radiation and chemotherapy (79,81,84).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal tissues, an increase in BIRC5 expression has been demonstrated in different types of cancers, including pancreatic (82), lung (83), colon and ovarian (84), esophageal and skin (85), colorectal and lymphoma (86) and prostate (87). In particular, in TNBC cells, the highly expressed BIRC5 is considered a marker in the early diagnosis of BC and was found to correlate with the resistance to radiation and chemotherapy (79,81,84). Additionally, two more apoptosis-related genes, DAPK1 and TP73 , were significantly downregulated in GOSS-treated MM-231 and MM-468 cells, respectively (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides breast cancer, BIRC5 detection has been related with prognosis and diagnosis of different human cancers such as acute lymphoblastic leukemia 29 , prolactinoma 30 , pancreatic cancer 31 and NSCLC 32,33 . Thus, BIRC5 overexpression is associated with adverse outcome in various cancers including breast, lung, colorectal, prostate, and ovarian cancer 34 and is considered to be one of the promising cancer diagnostic biomarker 3538 . It has been reported that urine BIRC5 levels can serve as a diagnostic marker in case of bladder cancer 39 and quantitative detection of BIRC5 in malignant pleural effusion can be useful in lung cancer diagnosis 40 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that urine BIRC5 levels can serve as a diagnostic marker in case of bladder cancer 39 and quantitative detection of BIRC5 in malignant pleural effusion can be useful in lung cancer diagnosis 40 . Recently, detection of serum BIRC5 levels has been found to be positively correlated with early diagnosis of different human cancers, including breast cancer 38 .…”
Section: Introductionmentioning
confidence: 99%